Crosslinked polyethylene for high-voltage cable and preparation method thereof
Through the combination of nanofiller masterbatch and specific additives, the breakdown problem of polyethylene cable insulation materials in high-voltage DC systems is solved, and high resistance to water tree aging and excellent mechanical properties are achieved, which is suitable for high-voltage cables.
Patent Information
- Application Number
- CN202510899281.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-01
- Publication Date
- 2025-08-05
- Estimated Expiration
- 2045-07-01
AI Technical Summary
The existing polyethylene cable insulation materials cannot be used in high-voltage DC systems, and are susceptible to the influence of local electric field strength to cause breakdown. The ionization and polarization of additives and crosslinked by-products under the DC electric field exacerbate the nonlinear change in conductivity, and lacks high space charge suppression ability.
Nanofilter masterbatches were used, including nanocd cadmium sulfide, nanostrinosterone barium titanate and carboxylated cellulose nanowhiskers, and nanofilter masterbatches were prepared by blending and extrusion. Tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]pentaerythritol tetramethyl[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid]pentaerythritol ester, 2,2,6,6-tetramethylpiperidine oxide, 4-propylene-2-hydroxybenzophenone, 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and tert-butyl peroxide isononanoate were added to form a three-dimensional network structure, inhibiting local discharge and oxidative degradation, and improving mechanical properties and breakdown strength.
It significantly improves the water tree aging resistance of cross-linked polyethylene, inhibits local discharge and oxidative degradation, improves tensile strength and breakdown strength, and ensures the stable operation of high-voltage cables.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cross-linked polyethylene, and in particular relates to cross-linked polyethylene for high-voltage cables and a preparation method thereof. Background Art
[0002] Polyethylene (PE) has a symmetrical molecular structure and is a non-polar material. Due to its high insulation resistance, good voltage resistance, low dielectric constant and dielectric loss, and minimal temperature and frequency effects, PE is widely used as the insulation material for power cables. Cross-linking significantly improves the mechanical and thermal properties of polyethylene, resulting in not only the same excellent electrical properties as thermoplastic polyethylene but also excellent mechanical properties at high temperatures. Its overall performance is significantly improved, particularly by raising the Vicat heat-resistant temperature by 30-40°C. The long-term operating temperature of cross-linked polyethylene (XLPE) is 95-100°C, and the long-term permissible operating temperature of XLPE cables can reach 90°C. In power systems, cross-linked polyethylene insulation, due to its excellent dielectric and heat-resistant properties, is widely used in high-voltage and ultra-high-voltage plastic-insulated power cables.
[0003] Due to the significant nonlinear variation in the electrical conductivity of insulating materials with temperature and field strength, existing polyethylene cable insulation materials can only be used for DC power transmission in low-voltage distribution systems and cannot be directly applied in high-voltage DC systems. Furthermore, local electric field strengths far exceed the operating strength of the cable, leading to direct breakdown of the cable material. Furthermore, the ionization and polarization of additives and crosslinking byproducts in the insulating material under DC electric fields exacerbate the nonlinear variation in electrical conductivity in polyethylene insulated cables. Therefore, the requirement for polyethylene cable insulation materials to possess high space charge suppression capabilities, resulting in high breakdown strength, and preventing polyethylene from experiencing breakdown aging has become a pressing technical challenge. Summary of the Invention
[0004] The purpose of the present invention is to provide a cross-linked polyethylene for high-voltage cables. The cross-linked polyethylene for high-voltage cables has excellent tensile strength and breakdown strength. The present invention also provides a preparation method thereof.
[0005] The cross-linked polyethylene for high-voltage cables of the present invention is composed of the following raw materials in parts by weight: 100 parts of low-density polyethylene, 3.5-4.5 parts of nanofiller masterbatch, 0.30-0.35 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.7-0.8 parts of 2,2,6,6-tetramethylpiperidinoxide, 0.7-0.8 parts of 4-propyleneoxy-2-hydroxybenzophenone, 100 parts of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne, 0. .0-1.2 parts and 0.8-1.0 parts of tert-butyl peroxyisononanoate, the preparation method of the nano filler masterbatch is: stirring and mixing nano cadmium sulfide, nano barium strontium titanate and titanate coupling agent NDZ-201 at room temperature for 13-15 minutes, then heating to 65-67 ° C and continuing to mix for 25-27 minutes to prepare a mixture, finally the carboxylated cellulose nano whiskers, the mixture and low-density polyethylene are blended and extruded in a twin-screw extruder, and the nano filler masterbatch is prepared after cooling and drying.
[0006] in: The manufacturer of carboxylated cellulose nanowhiskers is Qihong Technology Co., Ltd.
[0007] The mass of titanate coupling agent NDZ-201 accounts for 1.5% of the total mass of nano-cadmium sulfide and nano-barium strontium titanate.
[0008] The mass sum of nano-cadmium sulfide, nano-barium strontium titanate, carboxylated cellulose nanowhiskers and low-density polyethylene in the nanofiller masterbatch is 100%, among which nano-cadmium sulfide accounts for 7-9%, nano-barium strontium titanate accounts for 5-7%, carboxylated cellulose nanowhiskers accounts for 10-12% and low-density polyethylene accounts for 74-76%.
[0009] During the preparation of the nanofiller masterbatch, the stirring speed was 400 r / min, the blending extrusion temperature was 170°C, the cooling temperature was 20°C, the drying temperature was 80°C, and the drying time was 4 h.
[0010] The cross-linked polyethylene for high-voltage cables disclosed herein significantly improves its water-tree aging resistance by adding a nanofiller masterbatch. The semiconductor properties of nano-cadmium sulfide can partially conduct the electric field, reduce local electric field concentration, and inhibit discharge at the water-tree tip. Nano-barium strontium titanate is dispersed at the nanoscale to form an "electric field buffer layer," which reduces the electric field gradient and delays local discharge. The surface hydroxyl groups of carboxylated cellulose nanowhiskers can absorb ambient moisture, forming an internal humidity buffer layer during cable operation and reducing moisture penetration into the insulation layer. Thus, the synergistic effect of nano-cadmium sulfide, nano-barium strontium titanate, and carboxylated cellulose nanowhiskers improves the water-tree aging resistance of the prepared cross-linked polyethylene.
[0011] Preferably, the cross-linked polyethylene for high-voltage cable according to the present invention is composed of the following raw materials, in parts by weight: 100 parts of low-density polyethylene, 4.0 parts of nanofiller masterbatch, 0.33 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.75 parts of 2,2,6,6-tetramethylpiperidinoxide, 0.75 parts of 4-propyleneoxy-2-hydroxybenzophenone, 1.1 parts of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and 0.9 parts of tert-butyl peroxyisononanoate.
[0012] The method for preparing cross-linked polyethylene for high-voltage cables of the present invention comprises the following steps: (1) Preparation of nanofiller masterbatch; (2) Add low-density polyethylene and nanofiller masterbatch into a mixer and mix; (3) adding pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2,6,6-tetramethylpiperidinoxide and 4-propyleneoxy-2-hydroxybenzophenone to the mixture prepared in step (2) and mixing; (4) Cooling to 38-40°C, then adding tert-butyl peroxyisononanoate and 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and mixing; (5) The mixture obtained in step (4) is added to a single-screw extruder for extrusion and granulation, and then cooled and pelletized to prepare cross-linked polyethylene pellets. The cross-linked polyethylene pellets are added to a cable extruder for extrusion, and the extruded cable is passed into a saturated steam cross-linking pipeline for cross-linking, and then post-processed to prepare cross-linked polyethylene for high-voltage cable.
[0013] in: The mixing temperature in step (2) is 58-60°C and the mixing time is 5-7 minutes.
[0014] In step (3), the mixing speed is 300 r / min, the mixing temperature is 48-50° C., and the mixing time is 10-12 min.
[0015] In step (4), the mixing temperature is 38-40° C., the mixing time is 5-7 min, and the mixing speed is 150 r / min.
[0016] In step (5), the extrusion temperature of the single-screw extruder is 163-165°C, the cooling temperature is 20°C, the extrusion temperature of the cable extruder is 158-160°C, the cross-linking temperature in the saturated steam cross-linking pipe is 210-212°C, and the cross-linking time is 20-22 min.
[0017] The post-treatment in step (5) is to cool to 40°C by cold water circulation and then dry with hot air at 80°C for 12 hours to prepare cross-linked polyethylene for high-voltage cables.
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) The cross-linked polyethylene for high-voltage cables of the present invention is added with a nanofiller masterbatch to improve the water-tree aging resistance of the cross-linked polyethylene. By compounding pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 2,2,6,6-tetramethylpiperidinyl oxide, the molecular structure stability during the high-temperature cross-linking process is ensured while suppressing the oxidative degradation of the cross-linked polyethylene for high-voltage cables at high temperatures, thereby maintaining the electrical and mechanical properties of the cross-linked polyethylene for high-voltage cables. The added 4-propyleneoxy-2-hydroxybenzophenone has a strong electron affinity and can capture high-energy "hot electrons" generated by electron impact in an electric field environment, converting their kinetic energy into harmless heat energy through intramolecular proton transfer, blocking the electron avalanche effect, thereby suppressing the initiation of electrical treeing caused by local discharge and slowing down the accumulation of space charge at defects. A mixture of tert-butyl peroxyisononanoate and 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne is used as a cross-linking agent, and 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne is used as a free radical initiator to promote the cross-linking reaction of polyethylene, form chemical bonds between polyethylene molecular chains, thereby forming a three-dimensional network structure, and improve the heat resistance and mechanical properties of the prepared cross-linked polyethylene for high-voltage cables. Tert-butyl peroxyisononanoate is compounded to control the rate and degree of the cross-linking reaction. The free radicals generated by the decomposition of the two can complement and cooperate with each other, effectively initiating the cross-linking reaction of the polyethylene molecular chains, and improving the cross-linking efficiency and cross-linking degree.
[0019] (2) The cross-linked polyethylene for high-voltage cables described in the present invention uses a mixture of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and tert-butyl peroxy isononanoate as a cross-linking agent, wherein tert-butyl peroxy isononanoate first initiates decomposition at low temperature to generate highly active free radicals to initiate the cross-linking initiation reaction of the polyethylene main chain, thereby avoiding stress concentration caused by concentrated cross-linking in the high-temperature zone. 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne decomposes in the high-temperature zone to supplement free radicals and complete deep cross-linking, thereby improving cross-linking uniformity. At the same time, the amount of both is controlled to avoid excessive cross-linking leading to increased brittleness of the polyethylene.
[0020] (3) The cross-linked polyethylene for high-voltage cables of the present invention uses pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 2,2,6,6-tetramethylpiperidinyl oxide as antioxidants. Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] captures alkoxy radicals and peroxy radicals by providing active hydrogen to generate stable quinone compounds. However, it is easily oxidized and yellowed at high temperatures. Therefore, 2,2,6,6-tetramethylpiperidinyl oxide is used in combination. 2,2,6,6-tetramethylpiperidinyl oxide decomposes ROOH and regenerates phenols, reducing the accumulation of quinone substances and thus reducing yellowing. In addition, the nitro radical of 2,2,6,6-tetramethylpiperidinyl oxide can "capture" free radicals to generate polymer alkoxyamines, reducing the consumption of antioxidants caused by thermal oxidation aging of materials at low temperatures, and effectively inhibiting the scorching of cable insulation during extrusion.
[0021] (4) The cross-linked polyethylene for high-voltage cables of the present invention has excellent tensile strength and breakdown strength.
[0022] (5) The method for preparing cross-linked polyethylene for high-voltage cables of the present invention has easy-to-control process parameters, and the performance of the cross-linked polyethylene for high-voltage cables prepared is stable. DETAILED DESCRIPTION
[0023] Example 1 The cross-linked polyethylene for high-voltage cable described in Example 1 is composed of the following raw materials, in parts by weight: 100 parts of low-density polyethylene, 4.0 parts of nanofiller masterbatch, 0.33 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.75 parts of 2,2,6,6-tetramethylpiperidinoxide, 0.75 parts of 4-propyleneoxy-2-hydroxybenzophenone, 1.1 parts of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne, and 0.9 parts of tert-butyl peroxyisononanoate. The nanofiller masterbatch is prepared by stirring and mixing nano-cadmium sulfide, nano-barium strontium titanate, and titanate coupling agent NDZ-201 at room temperature for 14 minutes, then heating to 66° C. and continuing mixing for 26 minutes to prepare a mixture, and finally blending and extruding carboxylated cellulose nanowhiskers, the mixture, and low-density polyethylene in a twin-screw extruder, and cooling and drying to prepare the nanofiller masterbatch.
[0024] in: The manufacturer of carboxylated cellulose nanowhiskers is Qihong Technology Co., Ltd.
[0025] The mass of titanate coupling agent NDZ-201 accounts for 1.5% of the total mass of nano-cadmium sulfide and nano-barium strontium titanate.
[0026] The total mass of nano-cadmium sulfide, nano-barium strontium titanate, carboxylated cellulose nanowhiskers and low-density polyethylene in the nanofiller masterbatch is 100%, of which nano-cadmium sulfide accounts for 8%, nano-barium strontium titanate accounts for 6%, carboxylated cellulose nanowhiskers accounts for 11% and low-density polyethylene accounts for 75%.
[0027] During the preparation of the nanofiller masterbatch, the stirring speed was 400 r / min, the blending extrusion temperature was 170°C, the cooling temperature was 20°C, the drying temperature was 80°C, and the drying time was 4 h.
[0028] The method for preparing cross-linked polyethylene for high-voltage cables described in Example 1 comprises the following steps: (1) Preparation of nanofiller masterbatch; (2) Add low-density polyethylene and nanofiller masterbatch into a mixer and mix; (3) adding pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2,6,6-tetramethylpiperidinoxide and 4-propyleneoxy-2-hydroxybenzophenone to the mixture prepared in step (2) and mixing; (4) Cooling to 39°C, then adding tert-butyl isononanoate and 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and mixing; (5) The mixture obtained in step (4) is added to a single-screw extruder for extrusion and granulation, and then cooled and pelletized to prepare cross-linked polyethylene pellets. The cross-linked polyethylene pellets are added to a cable extruder for extrusion, and the extruded cable is passed into a saturated steam cross-linking pipeline for cross-linking, and then post-processed to prepare cross-linked polyethylene for high-voltage cable.
[0029] in: The mixing temperature in step (2) was 59° C. and the mixing time was 6 min.
[0030] In step (3), the mixing speed is 300 r / min, the mixing temperature is 49° C., and the mixing time is 11 min.
[0031] In step (4), the mixing temperature is 39° C., the mixing time is 6 min, and the mixing speed is 150 r / min.
[0032] In step (5), the extrusion temperature of the single-screw extruder is 164°C, the cooling temperature is 20°C, the extrusion temperature of the cable extruder is 159°C, the cross-linking temperature in the saturated steam cross-linking pipe is 211°C, and the cross-linking time is 20 min.
[0033] The post-treatment in step (5) is to cool to 40°C by cold water circulation and then dry with hot air at 80°C for 12 hours to prepare cross-linked polyethylene for high-voltage cables.
[0034] Example 2 The cross-linked polyethylene for high-voltage cable described in Example 2 is composed of the following raw materials, in parts by weight: 100 parts of low-density polyethylene, 3.5 parts of nanofiller masterbatch, 0.30 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.8 parts of 2,2,6,6-tetramethylpiperidinoxide, 0.8 parts of 4-propyleneoxy-2-hydroxybenzophenone, 1.0 parts of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne, and 0.8 parts of tert-butyl peroxyisononanoate. The nanofiller masterbatch is prepared by stirring and mixing nano-cadmium sulfide, nano-barium strontium titanate, and titanate coupling agent NDZ-201 at room temperature for 13 minutes, then heating to 65° C. and continuing mixing for 25 minutes to prepare a mixture, and finally blending and extruding the carboxylated cellulose nanowhiskers, the mixture, and low-density polyethylene in a twin-screw extruder, and cooling and drying to prepare the nanofiller masterbatch.
[0035] in: The manufacturer of carboxylated cellulose nanowhiskers is Qihong Technology Co., Ltd.
[0036] The mass of titanate coupling agent NDZ-201 accounts for 1.5% of the total mass of nano-cadmium sulfide and nano-barium strontium titanate.
[0037] The total mass of nano-cadmium sulfide, nano-barium strontium titanate, carboxylated cellulose nanowhiskers and low-density polyethylene in the nanofiller masterbatch is 100%, of which nano-cadmium sulfide accounts for 7%, nano-barium strontium titanate accounts for 7%, carboxylated cellulose nanowhiskers accounts for 10% and low-density polyethylene accounts for 76%.
[0038] During the preparation of the nanofiller masterbatch, the stirring speed was 400 r / min, the blending extrusion temperature was 170°C, the cooling temperature was 20°C, the drying temperature was 80°C, and the drying time was 4 h.
[0039] The method for preparing cross-linked polyethylene for high-voltage cables described in Example 2 comprises the following steps: (1) Preparation of nanofiller masterbatch; (2) Add low-density polyethylene and nanofiller masterbatch into a mixer and mix; (3) adding pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2,6,6-tetramethylpiperidinoxide and 4-propyleneoxy-2-hydroxybenzophenone to the mixture prepared in step (2) and mixing; (4) Cooling to 38°C, and then adding tert-butyl peroxyisononanoate and 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and mixing; (5) The mixture obtained in step (4) is added to a single-screw extruder for extrusion and granulation, and then cooled and pelletized to prepare cross-linked polyethylene pellets. The cross-linked polyethylene pellets are added to a cable extruder for extrusion, and the extruded cable is passed into a saturated steam cross-linking pipeline for cross-linking, and then post-processed to prepare cross-linked polyethylene for high-voltage cable.
[0040] in: The mixing temperature in step (2) was 58° C. and the mixing time was 5 min.
[0041] In step (3), the mixing speed is 300 r / min, the mixing temperature is 48° C., and the mixing time is 10 min.
[0042] In step (4), the mixing temperature is 38° C., the mixing time is 5 min, and the mixing speed is 150 r / min.
[0043] In step (5), the extrusion temperature of the single-screw extruder is 163°C, the cooling temperature is 20°C, the extrusion temperature of the cable extruder is 158°C, the cross-linking temperature in the saturated steam cross-linking pipe is 210°C, and the cross-linking time is 20 min.
[0044] The post-treatment in step (5) is to cool to 40°C by cold water circulation and then dry with hot air at 80°C for 12 hours to prepare cross-linked polyethylene for high-voltage cables.
[0045] Example 3 The cross-linked polyethylene for high-voltage cable described in Example 3 is composed of the following raw materials, in parts by weight: 100 parts of low-density polyethylene, 4.5 parts of nanofiller masterbatch, 0.35 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 0.7 parts of 2,2,6,6-tetramethylpiperidinyl oxide, 0.7 parts of 4-propyleneoxy-2-hydroxybenzophenone, 1.2 parts of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne, and 1.0 parts of tert-butyl peroxyisononanoate. The nanofiller masterbatch is prepared by stirring and mixing nano-cadmium sulfide, nano-barium strontium titanate, and titanate coupling agent NDZ-201 at room temperature for 15 minutes, then heating to 67° C. and continuing mixing for 27 minutes to prepare a mixture, and finally blending and extruding the carboxylated cellulose nanowhiskers, the mixture, and low-density polyethylene in a twin-screw extruder, and cooling and drying to prepare the nanofiller masterbatch.
[0046] in: The manufacturer of carboxylated cellulose nanowhiskers is Qihong Technology Co., Ltd.
[0047] The mass of titanate coupling agent NDZ-201 accounts for 1.5% of the total mass of nano-cadmium sulfide and nano-barium strontium titanate.
[0048] The total mass of nano-cadmium sulfide, nano-barium strontium titanate, carboxylated cellulose nanowhiskers and low-density polyethylene in the nanofiller masterbatch is 100%, of which nano-cadmium sulfide accounts for 9%, nano-barium strontium titanate accounts for 5%, carboxylated cellulose nanowhiskers accounts for 12% and low-density polyethylene accounts for 74%.
[0049] During the preparation of the nanofiller masterbatch, the stirring speed was 400 r / min, the blending extrusion temperature was 170°C, the cooling temperature was 20°C, the drying temperature was 80°C, and the drying time was 4 h.
[0050] The method for preparing cross-linked polyethylene for high-voltage cables described in Example 3 comprises the following steps: (1) Preparation of nanofiller masterbatch; (2) Add low-density polyethylene and nanofiller masterbatch into a mixer and mix; (3) adding pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2,6,6-tetramethylpiperidinoxide and 4-propyleneoxy-2-hydroxybenzophenone to the mixture prepared in step (2) and mixing; (4) Cooling to 40°C, and then adding tert-butyl peroxyisononanoate and 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and mixing; (5) The mixture obtained in step (4) is added to a single-screw extruder for extrusion and granulation, and then cooled and pelletized to prepare cross-linked polyethylene pellets. The cross-linked polyethylene pellets are added to a cable extruder for extrusion, and the extruded cable is passed into a saturated steam cross-linking pipeline for cross-linking, and then post-processed to prepare cross-linked polyethylene for high-voltage cable.
[0051] in: The mixing temperature in step (2) is 60° C. and the mixing time is 7 min.
[0052] In step (3), the mixing speed is 300 r / min, the mixing temperature is 50° C., and the mixing time is 12 min.
[0053] In step (4), the mixing temperature is 40° C., the mixing time is 7 min, and the mixing speed is 150 r / min.
[0054] In step (5), the extrusion temperature of the single-screw extruder is 165°C, the cooling temperature is 20°C, the extrusion temperature of the cable extruder is 160°C, the cross-linking temperature in the saturated steam cross-linking pipe is 212°C, and the cross-linking time is 20 min.
[0055] The post-treatment in step (5) is to cool to 40°C by cold water circulation and then dry with hot air at 80°C for 12 hours to prepare cross-linked polyethylene for high-voltage cables.
[0056] Comparative Example 1 The preparation method of the cross-linked polyethylene for high-voltage cables described in Comparative Example 1 is the same as that in Example 1, except that the raw material composition is different. The cross-linked polyethylene for high-voltage cables described in Comparative Example 1 is composed of the following raw materials, in parts by weight: 100 parts of low-density polyethylene, 0.33 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.75 parts of 2,2,6,6-tetramethylpiperidinyl oxide, 0.75 parts of 4-propyleneoxy-2-hydroxybenzophenone, 1.1 parts of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne, and 0.9 parts of tert-butyl peroxyisononanoate.
[0057] Comparative Example 2 The preparation method of the cross-linked polyethylene for high-voltage cables described in Comparative Example 2 is the same as that in Example 1, with the only difference being that the raw material composition is different. The cross-linked polyethylene for high-voltage cable described in Comparative Example 2 is composed of the following raw materials, in parts by weight: 100 parts of low-density polyethylene, 4.0 parts of nanofiller masterbatch, 0.33 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.75 parts of 2,2,6,6-tetramethylpiperidinoxide, 0.75 parts of 4-propyleneoxy-2-hydroxybenzophenone, 1.1 parts of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and 0.9 parts of tert-butyl peroxyisononanoate. The preparation method of the nanofiller masterbatch is as follows: nano-strontium barium titanate and titanate coupling agent NDZ-201 are stirred and mixed at room temperature for 14 minutes, then heated to 66°C and mixed for 26 minutes to prepare a mixture, and finally carboxylated cellulose nanowhiskers, the mixture and low-density polyethylene are blended and extruded in a twin-screw extruder, and the nanofiller masterbatch is prepared after cooling and drying.
[0058] in: The manufacturer of carboxylated cellulose nanowhiskers is Qihong Technology Co., Ltd.
[0059] The mass of titanate coupling agent NDZ-201 accounts for 1.5% of the mass of nano-barium strontium titanate.
[0060] The total mass of nano-barium strontium titanate, carboxylated cellulose nanowhiskers and low-density polyethylene in the nanofiller masterbatch is 100%, of which nano-barium strontium titanate accounts for 6%, carboxylated cellulose nanowhiskers account for 11% and low-density polyethylene accounts for 83%.
[0061] During the preparation of the nanofiller masterbatch, the stirring speed was 400 r / min, the blending extrusion temperature was 170°C, the cooling temperature was 20°C, the drying temperature was 80°C, and the drying time was 4 h.
[0062] Comparative Example 3 The preparation method of the cross-linked polyethylene for high-voltage cables described in Comparative Example 3 is the same as that in Example 1, with the only difference being that the raw material composition is different. The cross-linked polyethylene for high-voltage cable described in Comparative Example 3 is composed of the following raw materials, in parts by weight: 100 parts of low-density polyethylene, 4.0 parts of nanofiller masterbatch, 0.33 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.75 parts of 2,2,6,6-tetramethylpiperidinoxide, 0.75 parts of 4-propyleneoxy-2-hydroxybenzophenone, 1.1 parts of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and 0.9 parts of tert-butyl peroxyisononanoate; the preparation method of the nanofiller masterbatch is as follows: nano-cadmium sulfide and titanate coupling agent NDZ-201 are stirred and mixed at room temperature for 14 minutes, then the temperature is raised to 66°C and the mixing is continued for 26 minutes to prepare a mixture, and finally the carboxylated cellulose nanowhiskers, the mixture and the low-density polyethylene are blended and extruded in a twin-screw extruder, and the nanofiller masterbatch is prepared after cooling and drying.
[0063] in: The manufacturer of carboxylated cellulose nanowhiskers is Qihong Technology Co., Ltd.
[0064] The mass of titanate coupling agent NDZ-201 accounts for 1.5% of the mass of nano-cadmium sulfide.
[0065] The total mass of nano-cadmium sulfide, carboxylated cellulose nanowhiskers and low-density polyethylene in the nanofiller masterbatch is 100%, of which nano-cadmium sulfide accounts for 8%, carboxylated cellulose nanowhiskers accounts for 11% and low-density polyethylene accounts for 81%.
[0066] During the preparation of the nanofiller masterbatch, the stirring speed was 400 r / min, the blending extrusion temperature was 170°C, the cooling temperature was 20°C, the drying temperature was 80°C, and the drying time was 4 h.
[0067] Comparative Example 4 The preparation method of the cross-linked polyethylene for high-voltage cables described in Comparative Example 4 is the same as that in Example 1, with the only difference being that the raw material composition is different. The cross-linked polyethylene for high-voltage cable described in Comparative Example 4 is composed of the following raw materials, in parts by weight: 100 parts of low-density polyethylene, 4.0 parts of nanofiller masterbatch, 0.33 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.75 parts of 2,2,6,6-tetramethylpiperidinoxide, 0.75 parts of 4-propyleneoxy-2-hydroxybenzophenone, 1.1 parts of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and 0.9 parts of tert-butyl peroxyisononanoate; the preparation method of the nanofiller masterbatch is as follows: nano-cadmium sulfide, nano-barium strontium titanate and titanate coupling agent NDZ-201 are stirred and mixed at room temperature for 14 minutes, then the temperature is raised to 66°C and the mixing is continued for 26 minutes to prepare a mixture, and finally the mixture and low-density polyethylene are blended and extruded in a twin-screw extruder, and the nanofiller masterbatch is prepared after cooling and drying.
[0068] in: The mass of titanate coupling agent NDZ-201 accounts for 1.5% of the total mass of nano-cadmium sulfide and nano-barium strontium titanate.
[0069] The total mass of nano-cadmium sulfide, nano-barium strontium titanate and low-density polyethylene in the nano-filler masterbatch is 100%, of which nano-cadmium sulfide accounts for 8%, nano-barium strontium titanate accounts for 6% and low-density polyethylene accounts for 86%.
[0070] During the preparation of the nanofiller masterbatch, the stirring speed was 400 r / min, the blending extrusion temperature was 170°C, the cooling temperature was 20°C, the drying temperature was 80°C, and the drying time was 4 h.
[0071] The cross-linked polyethylene for high-voltage cables prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests. The tensile strength was measured in accordance with GB / T 1040-2006, and the breakdown strength was measured in accordance with the national standard GB / T 1408.1-1999. The test results are shown in Table 1 below: Table 1 Performance test results of cross-linked polyethylene for high voltage cables
[0072] The above test results show that the tensile strength and breakdown strength of the cross-linked polyethylene for high-voltage cables prepared in Examples 1-3 are significantly superior to those in Comparative Examples 1-4. Compared with Example 1, Comparative Examples 1-4 do not include the addition of nanofiller masterbatch. Compared with Example 1, Comparative Example 2 does not include the addition of nano-cadmium sulfide to the nanofiller masterbatch. Compared with Example 1, Comparative Example 3 does not include the addition of nano-barium strontium titanate to the nanofiller masterbatch. Compared with Example 1, Comparative Example 4 does not include the addition of carboxylated cellulose nanowhiskers to the nanofiller masterbatch. Compared with Example 1, the absence of the nanofiller masterbatch or the absence of some of the raw materials in the nanofiller masterbatch results in a decrease in the water tree aging resistance of the cross-linked polyethylene for high-voltage cables prepared in Comparative Examples 1-4, resulting in a decrease in the breakdown strength of the prepared cross-linked polyethylene.
Claims
1. A cross-linked polyethylene for high-voltage cables, characterized by: The invention is composed of the following raw materials in parts by weight: 100 parts of low-density polyethylene, 3.5-4.5 parts of nanofiller masterbatch, 0.30-0.35 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.7-0.8 parts of 2,2,6,6-tetramethylpiperidinoxide, 0.7-0.8 parts of 4-propyleneoxy-2-hydroxybenzophenone, 1.0-1.2 parts of 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne, and 0.8-1.0 parts of tert-butyl peroxyisononanoate. The preparation method of the nanofiller masterbatch is as follows: nano cadmium sulfide, nano barium strontium titanate and titanate coupling agent NDZ-201 are stirred and mixed at room temperature for 13-15 minutes, then heated to 65-67°C and continued to mix for 25-27 minutes to prepare a mixture, and finally carboxylated cellulose nano whiskers, the mixture and low-density polyethylene are blended and extruded in a twin-screw extruder, and the nanofiller masterbatch is prepared after cooling and drying.
2. The cross-linked polyethylene for high-voltage cables according to claim 1, characterized in that: The mass of titanate coupling agent NDZ-201 accounts for 1.5% of the total mass of nano-cadmium sulfide and nano-barium strontium titanate.
3. The cross-linked polyethylene for high-voltage cables according to claim 1, characterized in that: The mass sum of nano-cadmium sulfide, nano-barium strontium titanate, carboxylated cellulose nanowhiskers and low-density polyethylene in the nanofiller masterbatch is 100%, among which nano-cadmium sulfide accounts for 7-9%, nano-barium strontium titanate accounts for 5-7%, carboxylated cellulose nanowhiskers accounts for 10-12% and low-density polyethylene accounts for 74-76%.
4. The cross-linked polyethylene for high-voltage cables according to claim 1, characterized in that: During the preparation of the nanofiller masterbatch, the stirring speed was 400 r / min, the blending extrusion temperature was 170°C, the cooling temperature was 20°C, the drying temperature was 80°C, and the drying time was 4 h.
5. A method for preparing cross-linked polyethylene for high-voltage cables according to claim 1, characterized in that: It consists of the following steps: (1) Preparation of nanofiller masterbatch; (2) Add low-density polyethylene and nanofiller masterbatch into a mixer and mix; (3) adding pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2,6,6-tetramethylpiperidinoxide and 4-propyleneoxy-2-hydroxybenzophenone to the mixture prepared in step (2) and mixing; (4) Cooling to 38-40°C, then adding tert-butyl peroxyisononanoate and 2,5-dimethyl-2,5-di-tert-butylperoxy-3-hexyne and mixing; (5) The mixture obtained in step (4) is added to a single-screw extruder for extrusion and granulation, and then cooled and pelletized to prepare cross-linked polyethylene pellets. The cross-linked polyethylene pellets are added to a cable extruder for extrusion, and the extruded cable is passed into a saturated steam cross-linking pipeline for cross-linking, and then post-processed to prepare cross-linked polyethylene for high-voltage cable.
6. The method for preparing cross-linked polyethylene for high-voltage cables according to claim 5, characterized in that: The mixing temperature in step (2) is 58-60°C and the mixing time is 5-7 minutes.
7. The method for preparing cross-linked polyethylene for high-voltage cables according to claim 5, characterized in that: In step (3), the mixing speed is 300 r / min, the mixing temperature is 48-50° C., and the mixing time is 10-12 min.
8. The method for preparing cross-linked polyethylene for high-voltage cables according to claim 5, characterized in that: In step (4), the mixing temperature is 38-40° C., the mixing time is 5-7 min, and the mixing speed is 150 r / min.
9. The method for preparing cross-linked polyethylene for high-voltage cables according to claim 5, characterized in that: In step (5), the extrusion temperature of the single-screw extruder is 163-165°C, the cooling temperature is 20°C, the extrusion temperature of the cable extruder is 158-160°C, the cross-linking temperature in the saturated steam cross-linking pipe is 210-212°C, and the cross-linking time is 20-22 min.
10. The method for preparing cross-linked polyethylene for high-voltage cables according to claim 5, characterized in that: The post-treatment in step (5) is to cool to 40°C by cold water circulation and then dry with hot air at 80°C for 12 hours to prepare cross-linked polyethylene for high-voltage cables.
Citation Information
Patent Citations
Donor elements and processes for thermal transfer of nanoparticle layers
CN101517769A
Superfine barium strontium titanate nanofiber-based flexible film and preparation method thereof
CN113026146A
High-voltage cable for new energy vehicle
CN119286101A
Material for holding photocatalytic function and method of holding photocatalytic function
JP2001334148A
Curable composition comprising polyethylene and 2, 5-bis(t-butylperoxy)-2, 5-diphenylhexyne-3
US3334080A
Cited By
Heat-resistant light-weight cross-linked polyethylene insulated cable and preparation method thereof
CN121237485A
A heat-resistant lightweight crosslinked polyethylene insulated cable and a preparation method thereof
CN121237485B
